Why do Latin American firms hold so much more cash than they used to? - Perez Artica, Rodrigo (2019)
This study assesses whether the trade-off or the pecking order theories explain the increased cash ratios in Latin American firms. It also assesses the explanatory power of additional variables that identify key macroeconomic features in Latin American economies. Due to its noticeable increase, cash became a key feature of Latin American firm performance over the last decades. The need for a better understanding is stressed by the fact that, during most of the last decade, these firms experienced a phase of accelerated economic growth and buoyant financial markets. The resulting surge in real investment opportunities within this period makes the growing cash holdings all the more puzzling. As far as we know, no other research addresses this issue in a direct way. There are robust facts about the increased cash holdings in Latin American firms. This article assesses traditional explanations and defines which fits more properly to the study sample. A complementary explanation regarding exchange rate exposure and key macroeconomic variables is constructed and empirically evaluated. To address potential sources of endogeneity, dynamic panel data methods are used. Particularly, the system generalized method of moments (GMM) was applied, as proposed by Blundell and Bond (1998). This article reports an increasing trend for corporate cash holdings in a sample of selected Latin American firms between 2000 and 2014. Likewise, net leverage and short-term debt show a declining trend over the same period. The trade-off theory may explain this. A substantial effect of macroeconomic variables particularly affecting firms that operate in the region is observed, such as exchange rate risks.